Interventions for Indigenous Peoples Making Health Decisions: A Systematic Review - Jull, Janet; Crispo, James; Welch, Vivian; MacDonald, Heather; Brascoupe, Simon; Boyer, Yvonne; Stacey, Dawn (Université d'Ottawa | University of Ottawa, 2013)
Background: In general populations, shared decision making (SDM) facilitates care provider and consumer collaboration for informed health decisions. This study identifies SDM interventions to support Indigenous peoples making health decisions. Methods: A systematic review developed in dialogue with stakeholders using the Cochrane Handbook. A comprehensive search was conducted of electronic databases including all dates to present. Two independent researchers screened and quality appraised included studies. Findings were analyzed descriptively and reported using guidelines for equity focused systematic reviews. Results: Of 1,769 citations screened, 1 study was eligible for inclusion. This study was a randomized control trial rated as low quality for randomization and unclear for the other risk of bias criteria (allocation concealment, performance, detection, attrition, reporting bias). The study was conducted in the US with 44 students ages 11–13, and representative of Pueblo, Navajo, Hopi, and Jicarilla Apache Indian Nations. A culturally relevant tool assessed student decision-making skills before and after intervention. Students demonstrated increased decision making knowledge and were able to apply a four-step decision-making process to health situations. Conclusions: There is a lack of studies evaluating SDM among Indigenous peoples. One study demonstrated that a culturally relevant approach improved knowledge and application of decision-making skills. Further studies are needed.
Keywords: Indigenous peoples; Aboriginal peoples; children and youth; First Nations; Inuit; Métis; decision making; intervention studies; equity; systematic review